Penerapan Algoritma C4.5 Untuk Analisa Tingkat Keberhasilan Mahasiswa Dalam Pembelajaran Praktikum di Masa Pandemi - Dedy Hartama; Kristin Daya Rohani Sianipar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Practical learning is a method of learning in which students conduct experiments directly by applying the theories they have learned and proving what they have learned in order to better understand what they have learned. The success rate of students towards practical learning is one of the factors that can improve the quality of higher education and can facilitate lecture activities. To analyze the success rate of students towards practicum learning, they can use the C4.5 algorithm by looking at the highest gain. The C4.5 algorithm is one of the algorithms in data mining whose results are identical to the decision tree. Several parameters used for this research are motivation factor, learning method factor, learning material factor, and facility factor. This research was conducted with the aim of helping universities determine the level of student success in practicum learning using the C4.5 algorithm as much as 200 data. The results of the study showed an accuracy of 82.00% with the facility factor being the highest factor. So that the results obtained can help the campus in improving the learning process.